2015
DOI: 10.1002/clen.201400441
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Decolorization of Reactive Dye Solutions

Abstract: The most widely used dyes for coloration of cotton textiles are from reactive class. However, the large amount of unfixed dye causes color in the wastewater, which is environmentally unacceptable. Decolorization of various commercially important reactive dyes in aqueous solutions was attempted by microbial treatment using the bacteria Proteus vulgaris and Proteus mirabilis, individually as well as in a consortium. Different parameters such as treatment temperature, pH, dye solution concentration, and the seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Various methods employed to treat colored wastewater are chemical coagulation, activated carbon adsorption, chemical oxidation, photodecomposition, electrochemical treatment, reverse osmosis, hydrogen peroxide catalysis, etc. [4,5]. However, these methods are found to be less effective for various reasons such as higher cost and complexity of operation, generation of sludge as a secondary waste, ineffectiveness to treat wide range of color concentrations, inability of reuse, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods employed to treat colored wastewater are chemical coagulation, activated carbon adsorption, chemical oxidation, photodecomposition, electrochemical treatment, reverse osmosis, hydrogen peroxide catalysis, etc. [4,5]. However, these methods are found to be less effective for various reasons such as higher cost and complexity of operation, generation of sludge as a secondary waste, ineffectiveness to treat wide range of color concentrations, inability of reuse, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5]. However, these methods are found to be less effective for various reasons such as higher cost and complexity of operation, generation of sludge as a secondary waste, ineffectiveness to treat wide range of color concentrations, inability of reuse, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic dyes have harmful effects on the environment owing to their toxicity to microbes, hydrophytes, and animals. Thus, environmental protection acts have been enacted in most countries, which demand that textile waste must be treated before being released into natural water bodies [18]. It has now been proven that Lac can oxidize many synthetic dyes with high efficiency [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, dye removal rate mg/L•h was widely used for the comparison of dye removal performance by different biomass or bacteria (Franca et al, 2020). In this study, the removal rate of anthraquinone dye RB19 was around 2.6 -3.4 mg/L•h while 0.29-2.5 mg/L•h decolourization rates in the literature by using fungal isolates (Yemendzhiev et al, 2009;Attéké et al, 2013;Mounguengui et al, 2014) or consortium of Proteus mirabilis and Proteus vulgaris (Parmar and Shukla, 2015) were reported. Chaudhari et al (2017) reported 0.67-6.32 mg/L•h of anthraquinone dye RB4 at static conditions by using aerobic granules.…”
Section: Decolourisation Of Dyes In Sequencing Batch Cycles With/without Acetate Additionmentioning
confidence: 71%